Reconstruction Of Restorative Justice-Based Settlement Of Traffic Accident Offences - Helena, Lovita Aprillia; Hakim , Nur; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2025)
The approach to resolving criminal offences of traffic accidents in Indonesia has so far relied on a conventional criminal justice system that is oriented towards punishment. This approach often ignores victims' needs for recovery and opportunities for perpetrators to take constructive responsibility. This research aims to reconstruct a restorative justice-based traffic accident criminal settlement model, which emphasises dialogue, rapprochement and fair solutions for all parties involved. Using juridical-normative and juridical-empirical approaches, this research analyses existing regulations and legal settlement practices, as well as evaluates the potential of restorative justice implementation. The results show that restorative justice provides a great opportunity to create settlements that are more humane, inclusive, and in accordance with the local values of Indonesian society. The mediation process between offenders and victims, which is formally recognised in the justice system, is a key element in this model. The reconstruction of this model offers various benefits, such as victim recovery, reducing the burden on the justice system, and strengthening social harmony. However, its implementation requires adequate regulatory support, training for law enforcement officials, and education to the public. With these strategic steps, the application of restorative justice can be an effective solution in resolving traffic accidents, while reflecting the values of social justice in Pancasila.